Pengaruh Inklusi Keuangan Dan Pengelolaan Keuangan Terhadap Kinerja UMKM Sektor Kuliner Di Kecamatan Marpoyan Damai Pekanbaru - Netashah, Netashah; Ibrahim, Mariaty (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to determine the influence of Financial Inclusion and Financial Management on the Performance of MSMEs in the Culinary Sector in Marpoyan Damai District, Pekanbaru. The population in this study was 3,450 and there were 70 samples of business actors obtained using the Slovin formula.The research method used is a quantitative method and uses primary and secondary data. Primary data collection was carried out by distributing questionnaires to micro-entrepreneurs in the culinary sector in the Marpoyan Damai sub-district. To test the hypothesis in this research, use the SPSS version 25 program.The research results show that: 1) Financial inclusion has a significant effect on the performance of MSMEs, 2) Financial management has a significant effect on the performance of MSMEs, 3) Financial inclusion and financial management have a positive and significant effect on the performance of MSMEs.